Composite for secondary battery electrode
A composite for secondary battery electrodes with controlled nitrogen content and combustion temperature enhances fibrous carbon dispersion, addressing uniformity issues and resulting in high conductivity and improved battery performance.
Patent Information
- Application Number
- JP2023108269
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-06-30
AI Technical Summary
Existing methods for producing secondary battery electrodes face challenges in uniformly distributing fibrous carbon nanotubes, leading to non-uniform conductive networks and increased electrode resistance, which hinders the achievement of high conductivity and capacity.
A composite for secondary battery electrodes is developed, comprising fibrous carbon, a dispersant, and an active material, with a nitrogen content of 0.05 mol% to 10 mol% and a combustion temperature of fibrous carbon at 520°C or less, utilizing a copolymer with specific structural units to enhance adsorption and dispersion, thereby forming a uniform conductive path.
The composite achieves high conductivity and improved battery performance with reduced electrode resistance, enabling high-output and long-life nonaqueous electrolyte secondary batteries.
Smart Images

Figure 2025007095000001 
Figure 2025007095000002 
Figure 2025007095000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite for a secondary battery electrode, and an electrode, a secondary battery, and a device each using the composite. [Background technology]
[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and high performance of portable devices, secondary batteries with high energy density and higher capacity are required. Under such a background, non-aqueous electrolyte secondary batteries using a non-aqueous electrolyte, particularly lithium ion secondary batteries, are being used in many devices because of their characteristics of high energy density and high voltage.
[0003] The electrodes of secondary batteries are prepared by coating a composite slurry containing a positive electrode active material or a negative electrode active material, a conductive material, a binder resin, etc., on a current collector. A conductive material dispersion liquid in which a conductive material is dispersed in a dispersion medium is prepared, and an active material and a binder resin are added to the conductive material dispersion liquid to prepare a composite slurry, so that the conductive material is uniformly dispersed and contained in the electrode film, and the conductivity of the electrode film can be improved. In order to increase the capacity of secondary batteries, an increase in the ratio of active materials in the electrodes is desired, and carbon nanotubes, which can efficiently form a conductive network even with a small amount as a conductive agent and reduce electrode resistance, are considered promising. On the other hand, in order to achieve low resistance with the addition of a smaller amount of carbon nanotubes, it is effective to use carbon nanotubes with a small average outer diameter and large fiber length. However, these carbon nanotubes have strong cohesive forces, making it difficult to distribute them uniformly in the electrode. In order to efficiently form a conductive network in the electrode and ensure a conductive path to the active material, a method has been proposed in which a composite is used in which a conductive material such as carbon nanotubes is adsorbed onto the surface of the active material in advance.
[0004] Patent Documents 1 and 2 disclose examples of producing composite particles for electrochemical device electrodes with low resistance and high capacity by combining a positive electrode active material, acetylene black, and an acrylate polymer by spray drying. Patent Document 3 discloses an example of manufacturing a thin-film electrode structure having low resistance and excellent film strength by dispersing and combining an electrode material and single-walled carbon nanotubes using a mill and ultrasonic homogenizer. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent 6954424 [Patent Document 2] Patent 6760065 [Patent Document 3] Patent 7198331 Summary of the Invention [Problem to be solved by the invention]
[0006] The methods disclosed in Patent Documents 1 and 2 use a dispersion of acetylene black as a conductive assistant, making it difficult to form an efficient conductive network with a small amount of addition compared to when fibrous carbon is used as a conductive assistant. In the method disclosed in Patent Document 3, it is difficult to disentangle the fibrous and entangled carbon nanotubes during the composite formation process, and because the method does not contain a dispersing resin, the carbon nanotubes are not uniformly adsorbed onto the active material surface, resulting in a non-uniform composite, making it difficult to form a uniform conductive network in the electrode.
[0007] In order to solve the above problems, the present invention aims to provide a composite for secondary battery electrodes, which can achieve high conductivity in the electrode by uniformly dispersing the fibrous carbon on the active material when the active material and fibrous carbon are combined, thereby improving the adsorption between the active material and the fibrous carbon. [Means for solving the problem]
[0008] The present invention relates to a composite for a secondary battery electrode, which contains fibrous carbon, a dispersant, and an active material, and is characterized in that the amount of nitrogen element measured by X-ray photoelectron spectroscopy is 0.05 mol % or more and 10 mol % or less.
[0009] The present invention relates to a composite for a secondary battery electrode, wherein the fibrous carbon contained in the composite for a secondary battery electrode has an exothermic peak temperature of 520° C. or less, as measured in the presence of oxygen by simultaneous thermogravimetry-differential thermal analysis.
[0010] The present invention relates to the above composite for a secondary battery electrode, comprising a dispersant which contains a copolymer including an aliphatic hydrocarbon structural unit and a nitrile group-containing structural unit, the aliphatic hydrocarbon structural unit including an alkylene structural unit, the content of the aliphatic hydrocarbon structural unit being 40% by mass or more and less than 85% by mass based on the mass of the copolymer, and the content of the nitrile group-containing structural unit being 15% by mass or more and 50% by mass or less based on the mass of the copolymer.
[0011] The present invention relates to the above composite for a secondary battery electrode, wherein the copolymer further contains 10 mass % or less of alkyl group-substituted or unsubstituted carbamoyl group-containing structural units based on the mass of the copolymer.
[0012] The present invention relates to a composite for a secondary battery electrode, characterized in that the amount of elemental nitrogen measured by X-ray photoelectron spectroscopy is 0.3 mol % or more and 3 mol % or less.
[0013] The present invention relates to a method for producing a composite for a secondary battery electrode, which further comprises a binder resin.
[0014] The present invention also relates to an electrode for a secondary battery comprising the above-mentioned composite for a secondary battery electrode.
[0015] The present invention relates to a secondary battery including the secondary battery electrode.
[0016] The present invention relates to a vehicle or device equipped with the secondary battery.
[0017] The present invention relates to a method for producing a composite for a secondary battery electrode, the method comprising the steps of: combining a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent with an electrode active material using a mixing device; and removing the solvent and drying the composite. Effect of the Invention
[0018] According to an embodiment of the present invention, it is possible to precisely control the dispersion state of the fibrous carbon on the active material by including a nitrogen element, and it is possible to provide a composite for a secondary battery electrode having excellent electrical conductivity. According to yet another embodiment of the present invention, it is possible to provide a high-output, long-life non-aqueous electrolyte secondary battery and an electrode film used therein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, a method for producing a composite for a secondary battery electrode according to an embodiment of the present invention will be described in detail. The present invention is not limited to the following embodiment, and the present invention also includes embodiments that are implemented within the scope of the present invention.
[0020] In this specification, carbon nanotubes may be referred to as "CNTs." Hydrogenated nitrile rubber may be referred to as "H-NBR," and N-methyl-2-pyrrolidone may be referred to as "NMP." In this specification, carbon nanotube dispersions may be simply referred to as "CNT dispersions" or "dispersions." Additionally, composites for secondary battery electrodes may be referred to as "composite for electrodes" or "composite."
[0021] <Composite for secondary battery electrodes> The composite for a secondary battery electrode contains an electrode active material and fibrous carbon, and may further contain an optional dispersant and a binder resin. The composite for an electrode may further contain optional components.
[0022] The nitrogen element content of the secondary battery electrode composite of the present invention can be confirmed by X-ray photoelectron spectroscopy (XPS). In this specification, X-ray photoelectron spectroscopy may be referred to as "XPS".
[0023] The composite for secondary battery electrodes contains a nitrogen element. The nitrogen element is preferably contained in an optional component other than the electrode active material and the fibrous carbon. The non-shared electron pair of nitrogen contained in the optional nitrogen-containing compound interacts with the benzene ring structure of the fibrous carbon and the electrode active material to adsorb. Therefore, it is believed that a conductive path can be more efficiently established between the electrode active material and the fibrous carbon by firmly adsorbing the fibrous carbon and the electrode active material via the nitrogen-containing compound. This improves the rate characteristics and cycle characteristics. The nitrogen-containing compound is preferably a component contained in the process of mixing the electrode active material and the fibrous carbon, and examples of such components include a dispersant, a binder resin, and other additives described below.
[0024] When the nitrogen element content of the composite for secondary battery electrodes is 10 mol% or less, a secondary battery electrode with excellent conductivity can be produced. It is preferably 3 mol% or less, and more preferably 1.5 mol% or less. It is also preferably 0.05 mol% or more, more preferably 0.1 mol% or more, and more preferably 0.5 mol% or more. If it is 10 mol% or more, the resin component in the electrode becomes large, which leads to deterioration of the electrode resistance. If it is 0.05 mol% or less, the adsorptive force decreases and the active material and the fibrous carbon are dissociated, which leads to deterioration of the electrode resistance. The nitrogen element content can be adjusted by adjusting the blending amount of the nitrogen-containing compound, etc.
[0025] When the combustion temperature of the fibrous carbon in an oxygen-containing atmosphere is 520° C. or lower, the electrode composite of the present invention becomes a composite in a homogeneous state in which the fibrous carbon adsorbed on the active material surface is loosened.
[0026] The temperature of the exothermic peak in the present invention can be determined by TG-DTA (Thermogravimetry-Differential Thermal Analysis) measurement. Specifically, a TG curve and a DTA curve are obtained by performing TG-DTA measurement under air or oxygen flow conditions. In the obtained DTA curve, the top of the maximum exothermic peak resulting from the combustion of the fibrous carbon, which is located in the vicinity of 300 to 600°C, is read and determined as the temperature of the exothermic peak of the fibrous carbon. This represents the combustion temperature of the fibrous carbon. Generally, fibrous carbon has thick bundles in which primary particles are strongly aggregated by van der Waals forces, and large secondary aggregates in which bundles are aggregated together. The physical properties, such as thermal stability, differ depending on the state of aggregation. Therefore, even for the same type of fibrous carbon, the combustion temperature changes depending on the state of aggregation, and the stronger the aggregation, the higher the combustion temperature.
[0027] The combustion temperature of the fibrous carbon in the secondary battery electrode composite in an oxygen-containing atmosphere is preferably 520°C or less, since the fibrous carbon on the active material is adsorbed in a more loose state, which favors the formation of an electron conduction path from the fibrous carbon to the active material and improves the battery characteristics. It is preferably 480°C or less, and more preferably 450°C or less.
[0028] As described above, when the amount of nitrogen measured by X-ray photoelectron spectroscopy is 0.05 mol% or more and 10 mol% or less and the combustion temperature is 520°C or less, the fibrous carbon in the composite is crushed and thinly adsorbed on the active material, and when the composite is used as an electrode for a secondary battery, the electrode resistance is reduced and the formation of an electronic conduction path to the active material during the battery reaction is favorable, and the battery rate characteristics and cycle characteristics can be improved, which is preferable. In addition, since an efficient conductive path can be formed with a small amount of conductive additive, the amount of conductive additive in the electrode can be reduced, and the battery capacity can be improved.
[0029] <Active material> The active material is a material that causes a battery reaction required to extract electrical energy, and is not particularly limited. For example, for secondary battery applications, metal compounds such as metal oxides and metal sulfides that can reversibly dope or intercalate lithium ions can be used as the positive electrode active material. For example, lithium manganese composite oxides (e.g., Li x Mn2O4 or Li x MnO2), lithium nickel composite oxide (e.g. Li x NiO2), lithium cobalt complex oxide (Li x CoO2), lithium nickel cobalt complex oxide (e.g. Li x Ni 1-y Co y O2), lithium manganese cobalt complex oxide (e.g. Li x Mn y Co 1-y O2), lithium nickel manganese cobalt composite oxide (e.g. Li x Ni y Co z Mn 1-y-z O2), spinel-type lithium manganese nickel composite oxide (e.g. Li x Mn 2-y Ni y O4), lithium phosphate powder with an olivine structure (e.g. Li x FePO4, Li x Fe 1-y Mn y PO4, Li x CoPO4, etc.), manganese oxide, iron oxide, copper oxide, nickel oxide, vanadium oxide (e.g. V2O5, V6O 13) Examples include transition metal oxide powders such as titanium oxide, transition metal sulfide powders such as iron(III) sulfate (Fe2(SO4)3), TiS2, and FeS. However, x, y, and z are numbers, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and 0 < y + z < 1. These cathode active materials can also be used alone or in combination. Among these active materials, in particular, active materials containing Ni and / or Mn (especially when the total amount of Ni and / or Mn in the transition metal is 50 mol% or more) tend to become highly basic due to components derived from the raw materials or elution of metal ions, and as a result, gelation of the binder resin and deterioration of the dispersion state are likely to occur. Therefore, in the case of a battery containing an active material containing Ni and / or Mn, this embodiment is particularly effective.
[0030] As the anode active material, for example, metallic Li that can reversibly dope or intercalate lithium ions, or an alloy thereof, a tin alloy, a silicon-based material (such as metallic Si, Si alloy, SiOx), a metal oxide-based material such as LiXTiO2, LiXFe2O3, LiXFe3O4, LiXWO2, a conductive polymer such as polyacetylene or poly-p-phenylene, artificial graphite such as highly graphitized carbon material, or a carbonaceous powder such as natural graphite, or a resin-fired carbon material can be used. However, x is a number, where 0 < x < 1. These anode active materials can also be used alone or in combination. In particular, when using a silicon-based material, although the theoretical capacity is large, the volume expansion is extremely large. Therefore, it is preferably used in combination with artificial graphite such as highly graphitized carbon material, or a carbonaceous powder such as natural graphite, or a resin-fired carbon material.
[0031] <Fibrous carbon> Fibrous carbon is a fibrous carbon material, and has a high aspect ratio in the long axis direction, making it easier to form a conductive network compared to particulate carbon such as carbon black. Examples of fibrous carbon include carbon fiber (CNF) and carbon nanotube (CNT). CNTs are flat graphite rolled into a cylindrical shape, and include single-walled CNTs, double-walled CNTs, thin-walled (several-walled) CNTs, and multi-walled CNTs, and these may be mixed. Single-walled CNTs have a structure in which one layer of graphite is rolled. Multi-walled CNTs have a structure in which two or more layers of graphite are rolled. In addition, the sidewalls of CNTs do not have to have a graphite structure. In addition, for example, CNTs with sidewalls having an amorphous structure are also CNTs in this specification.
[0032] The shape of the CNT is not limited. Examples of such shapes include various shapes including needle-like, cylindrical tube-like, fishbone-like (fishbone or cup stack type), trump-like (platelet) and coil-like. Among them, the shape of the CNT is preferably needle-like or cylindrical tube-like. The CNT may be a single shape or a combination of two or more shapes.
[0033] Examples of the form of CNT include graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers. The carbon nanotubes may have a single form or a combination of two or more of these forms.
[0034] The average outer diameter of the fibrous carbon is preferably 100 nm or less, more preferably 50 nm or less. If the average outer diameter is too large, it becomes difficult to adjust the volume resistivity to 100 Ω·cm or less. In addition, it is preferably 30 nm or less, more preferably 20 nm or less, and even more preferably 13 nm or less. In addition, it is preferably 1 nm or more, and more preferably 3 nm or more. The average outer diameter of the fibrous carbon can be calculated by first observing and photographing the fibrous carbon with a transmission electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the outer diameter of each piece.
[0035] The content of fibrous carbon in the composite is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.05% by mass or more, based on the mass of the composite. Also, it is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. If it exceeds the above range, the amount of active material filled in the electrode decreases, resulting in a decrease in battery capacity. In particular, for high-capacity batteries, 10% by mass or less is preferable. If it is below the above range, the conductivity of the electrode and battery may be insufficient.
[0036] The composite may contain a conductive material other than fibrous carbon. Examples of the other conductive material include carbon materials such as carbon black, fullerene, graphene, multilayer graphene, and graphite. The carbon black may be neutral, acidic, or basic, and may be oxidized carbon black or graphitized carbon black. The other conductive materials may be used alone or in combination of two or more.
[0037] <Binder resin> The composite of the present invention may contain a binder resin as necessary. The binder resin is not particularly limited as long as it is normally used as a binder resin, and can be appropriately selected according to the purpose. The binder resin used in the composite is preferably a resin capable of binding between substances such as active materials and fibrous carbon. Examples of the binder resin used in the composite include polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, styrene, etc. as structural units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, and fluororesins; cellulose-based resins such as carboxymethylcellulose; elastomers such as styrene-butadiene rubber and fluororubber; and conductive resins such as polyaniline and polyacetylene. Modifications of these resins are also possible. The resin may be a polymer, a mixture, or a copolymer. Particularly, fluororesins are preferred, and examples thereof include polytetrafluoroethylene (PTFE), polyvinyl fluoride (PVF), polyvinylidene fluoride (PVDF), and modified products thereof. These may be used alone or in combination of two or more. Among these, from the viewpoint of resistance, polymers or copolymers having fluorine atoms in the molecule, such as polyvinylidene fluoride, polyvinyl fluoride, tetrafluoroethylene, resins having these structural units, and modified products thereof are preferred.
[0038] The content of the binder resin in the composite is preferably 0.1% by mass or more, and more preferably 0.3% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass), and is preferably 20% by mass or less, and more preferably 10% by mass or less.
[0039] <Method of manufacturing a composite for secondary battery electrode> The method for compounding the positive electrode active material with the fibrous carbon, etc. is not particularly limited. For example, a method of mixing the active material with the fibrous carbon, etc. in a dry state, a method of further adding a solvent and mixing, a method of preparing a slurry and mixing in a wet state, etc. can be mentioned. In order to prepare a more uniform composite, a method of mixing using a dispersion liquid in which fibrous carbon or the like is dispersed in a solvent in advance is preferred. Among them, the use of a fibrous carbon dispersion is preferred because it allows the preparation of an electrode composite in which the active material and fibrous carbon are uniformly combined. Even if a fibrous carbon dispersion is not used, it is preferred because the same effect can be obtained by breaking up the agglomerates of the fibrous carbon using a high shear force composite machine or the like. The combination of a fibrous carbon dispersion and a high shear force composite machine is particularly preferred.
[0040] Examples of dry mixers include: Examples of such equipment include roll mills with two or three rolls, high-speed agitators such as Henschel Mixers and Super Mixers, fluid energy grinders such as Micronizers and Jet Mills, attritors, particle composite devices manufactured by Hosokawa Micron Corporation such as "Nanocure," "Nobilta," and "Mechanofusion," powder surface modification devices manufactured by Nara Machinery Manufacturing Co., Ltd. such as "Hybridization System," "Mechano Micros," and "Miraro," mixers manufactured by Inoue Manufacturing Co., Ltd. such as "Planetary Mixer" and "Trimix," and mixer / granulator "High Speed Mixer" manufactured by EarthTechnica.
[0041] In addition, when using a dry mixer, other raw materials such as fibrous carbon may be added directly in powder form to the active material as the base material, but in order to create a more uniform mixture, it is preferable to disperse or dissolve the other raw materials such as fibrous carbon in a small amount of solvent in advance and then mix them. Among these, the use of a fibrous carbon dispersion is preferable because it allows the preparation of an electrode composite in which the active material and fibrous carbon are uniformly combined. Furthermore, in order to increase the processing efficiency, it may be preferable to heat the mixture. Among dry mixers, a planetary mixer, trimix, or mechanofusion, which is capable of compounding by shearing, is preferable.
[0042] Examples of wet mixing devices include: Mixers such as dispersers, homomixers, or planetary mixers; Homogenizers such as "Clearmix" manufactured by M Techniques or "Filmix" manufactured by PRIMIX; Rotation and revolution type mixers such as THINKY's "Awatori Rentaro" Media-type dispersing machines such as a paint conditioner (manufactured by Red Devil), a ball mill, a sand mill (such as "Dyno Mill" manufactured by Shinmaru Enterprises), an attritor, a pearl mill (such as "DCP Mill" manufactured by Eirich), or a Coball mill; Wet jet mills (such as Genus PY, Sugino Machine Starburst, and Nanomizer), M-Technique Claire SS-5, and Nara Machinery Micros media-less dispersers; Other examples include, but are not limited to, roll mills, kneaders, etc. In addition, it is preferable to use a wet mixing device that has been treated to prevent metal from entering the device. When a media-type dispersing machine such as a ball mill is used, there is a risk that the structure of the active material may be destroyed by mixing, so a media-less dispersing machine is preferred.
[0043] Examples of the method for removing the solvent and drying include hot air drying, vacuum drying, spray drying, freeze drying, etc. Among these, hot air drying and vacuum drying are preferred from the viewpoint of productivity.
[0044] <Carbon fiber dispersion> The fibrous carbon dispersion contains fibrous carbon and a dispersion medium, and optionally contains a dispersant. The fibrous carbon dispersion may contain optional components such as wetting agents, surfactants, pH adjusters, wetting penetrants, other additives such as leveling agents, other conductive materials, and other polymer components, as necessary, within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the dispersion, during dispersion, after dispersion, or a combination thereof.
[0045] The dispersibility of the fibrous carbon in the fibrous carbon dispersion can also be evaluated by the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer. With the median diameter (μm) determined by a laser diffraction / scattering type particle size distribution analyzer, the particle diameter of the fibrous carbon aggregated particles can be estimated by the distribution of scattered light intensity by the particles. The median diameter (μm) is preferably 0.4 μm or more, and is preferably 5.0 μm or less, and more preferably 2.0 μm or less. By setting it within the above range, a fibrous carbon dispersion in an appropriate dispersion state can be obtained. If it is below the above range, fibrous carbon in an aggregated state will exist, and if it exceeds the above range, a large number of finely cut fibrous carbons will be generated, making it difficult to form an efficient conductive network. The median diameter can be measured by the method described in the examples.
[0046] The viscosity of the fibrous carbon dispersion, measured using a B-type viscometer at 25°C and 60 rpm, is preferably 10 mPa·s or more and less than 10,000 mPa·s, more preferably 10 mPa·s or more and less than 2,000 mPa·s, and even more preferably 10 mPa·s or more and less than 1,000 mPa·s.
[0047] The TI value of the fibrous carbon dispersion can be calculated by dividing the viscosity (mPa·s) at 6 rpm measured at 25°C with a B-type viscometer by the viscosity (mPa·s) at 60 rpm. The TI value is preferably 1.0 or more and less than 10.0, more preferably 1.0 or more and less than 5.0, and even more preferably 1.0 or more and less than 3.0. The higher the TI value, the greater the structural viscosity due to the entanglement of the fibrous carbon, dispersant, and other resin components, or the intermolecular forces thereof, and the lower the TI value, the smaller the structural viscosity. By setting the TI value within the above range, the entanglement of the fibrous carbon, dispersant, and other resin components can be suppressed while allowing these intermolecular forces to act appropriately.
[0048] The average fiber length of the fibrous carbon in the fibrous carbon dispersion is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the fibrous carbon in the fibrous carbon dispersion can be calculated by diluting the fibrous carbon dispersion 50 times with a non-aqueous solvent such as NMP, dropping the diluted fibrous carbon dispersion onto a substrate, drying the diluted fibrous carbon dispersion, observing the sample with a scanning electron microscope, and randomly selecting 300 pieces of fibrous carbon from the observation photograph and measuring the fiber length of each piece.
[0049] The content of the fibrous carbon is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and more preferably 0.8% by mass or more, based on the total amount of the fibrous carbon dispersion. Also, it is preferably 20% by mass or less, and more preferably 10% by mass or less. By setting it within the above range, the fibrous carbon can be present well and stably without causing sedimentation or gelation. It is more preferably 0.1 to 20% by mass, and even more preferably 0.5 to 10% by mass. Also, it is preferable that the content of the fibrous carbon is appropriately adjusted so that a fibrous carbon dispersion liquid with appropriate fluidity or viscosity is obtained depending on the specific surface area of the fibrous carbon, affinity to the dispersion medium, dispersibility of the dispersant, etc.
[0050] The content of the dispersant is preferably 5 to 200 parts by mass, more preferably 10 to 100 parts by mass, and even more preferably 15 to 80 parts by mass, relative to 100 parts by mass of the fibrous carbon. The content of the dispersant is preferably 0.1 to 10% by mass, and more preferably 0.5 to 5% by mass, relative to the total amount of the fibrous carbon dispersion.
[0051] The solid content of the fibrous carbon dispersion is preferably from 0.2 to 40 mass %, more preferably from 0.5 to 20 mass %, and further preferably from 1 to 10 mass %.
[0052] The fibrous carbon dispersion may be prepared by separately preparing two or more kinds of fibrous carbon having different average outer diameters and adding them to a dispersion medium. When two or more kinds of fibrous carbon having different average outer diameters are used as the fibrous carbon, the average outer diameter of the first fibrous carbon is preferably 1 nm or more and less than 5 nm. The average outer diameter of the second fibrous carbon is preferably 5 nm or more and 30 nm or less, more preferably 20 nm or less. When two or more kinds of fibrous carbon having different average outer diameters are used as the fibrous carbon, the mass ratio of the first fibrous carbon to the second fibrous carbon is preferably 1:10 to 1:100, more preferably 1:10 to 1:50.
[0053] The average fiber length of the fibrous carbon is preferably 0.5 μm or more, more preferably 0.8 μm or more, and even more preferably 1.0 μm or more. Also, it is preferably 20 μm or less, and more preferably 10 μm or less. The average fiber length of the fibrous carbon can be calculated by first observing and photographing the fibrous carbon with a scanning electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the fiber length of each piece.
[0054] The aspect ratio is the fiber length of the fibrous carbon divided by the outer diameter. A representative aspect ratio can be calculated using the average fiber length and the average outer diameter. A conductive material with a higher aspect ratio can provide higher conductivity when formed into an electrode. The aspect ratio of the fibrous carbon is preferably 30 or more, more preferably 50 or more, and even more preferably 80 or more. In addition, it is preferably 10,000 or less, more preferably 3,000 or less, and even more preferably 1,000 or less.
[0055] The specific surface area of fibrous carbon is 100m 2 / g or more, and 150m 2 / g or more is more preferable, and 200m 2 / g or more is more preferable. 2 / g or less, and2 / g or less is more preferable. The specific surface area of the fibrous carbon is calculated by the BET method using nitrogen adsorption measurement. When the average outer diameter, average fiber length, aspect ratio, and specific surface area of the fibrous carbon are within the above ranges, a conductive path developed in the electrode is easily formed.
[0056] The carbon purity of the fibrous carbon is represented by the content (mass%) of carbon atoms in the fibrous carbon, and is preferably 80 mass% or more relative to 100 mass% of the fibrous carbon.
[0057] For the purpose of removing or reducing impurities such as metal catalysts and increasing the carbon purity, fibrous carbon that has been subjected to a purification treatment may be used.
[0058] When fibrous carbon is dispersed in a disperser by collision with media such as a bead mill, or when it is repeatedly passed through a disperser over a long period of time, the fibrous carbon may be broken and short-flaked carbonaceous matter may be generated. When short-flaked carbonaceous matter is generated, the viscosity of the fibrous carbon dispersion decreases, and the gloss of the coating film obtained by coating and drying the fibrous carbon dispersion increases. Judging from these evaluation results alone, however, the short-flaked carbonaceous matter has high contact resistance and is difficult to form a conductive network, which may worsen the resistance of the electrode. The degree of short-flaked carbonaceous matter generation can be confirmed by diluting the dispersion liquid, dropping it onto a substrate with a smooth surface and good affinity with the dispersion medium, and drying the sample, and observing it with a scanning electron microscope. By adjusting the dispersion conditions and the composition of the dispersion liquid so that carbonaceous matter of 0.1 μm or less is not generated, an electrode with high conductivity can be obtained.
[0059] The fibrous carbon may be produced by any method. The fibrous carbon can generally be produced by, but is not limited to, a laser ablation method, an arc discharge method, a thermal CVD method, a plasma CVD method, and a combustion method. For example, the fibrous carbon can be produced by contacting a carbon source with a catalyst at 500 to 1000°C in an atmosphere with an oxygen concentration of 1% by volume or less. The carbon source may be at least one of a hydrocarbon and an alcohol.
[0060] <Dispersant> The dispersant for the fibrous carbon dispersion is preferably one that can disperse and stabilize the fibrous carbon in the fibrous carbon dispersion. The dispersant may be either a resin-type dispersant or a surfactant, but a resin-type dispersant is preferred because it has a strong adsorption power to the fibrous carbon and can provide good dispersion stability. Depending on the characteristics required for dispersing the fibrous carbon, a suitable type of dispersant can be used in a suitable amount.
[0061] Examples of the resin-type dispersant that can be used include (meth)acrylic polymers, polymers derived from ethylenically unsaturated hydrocarbons, cellulose derivatives, and copolymers thereof. Examples of the polymers derived from ethylenically unsaturated hydrocarbons include polyvinyl alcohol resins, polyvinylpyrrolidone resins, polyacrylonitrile resins, and nitrile rubbers. Examples of the polyvinyl alcohol resins include polyvinyl alcohol, modified polyvinyl alcohols having functional groups other than hydroxyl groups (e.g., acetyl groups, sulfo groups, carboxy groups, carbonyl groups, and amino groups), polyvinyl alcohols modified with various salts, other anion- or cation-modified polyvinyl alcohols, and polyvinyl acetals (polyvinyl acetoacetal, polyvinyl butyral, etc.) modified with acetal (acetoacetal-modified or butyral-modified, etc.) by aldehydes. The polyacrylonitrile resin may be a homopolymer of polyacrylonitrile, a copolymer of polyacrylonitrile, or a modified product thereof. A polyacrylonitrile resin having at least one selected from the group consisting of active hydrogen groups such as hydroxyl groups, carboxy groups, primary amino groups, secondary amino groups, and mercapto groups, basic groups, (meth)acrylic acid alkyl esters, or alkyl groups derived from α-olefins, etc. is preferred. For example, the acrylonitrile copolymer described in JP-A-2020-163362 can be used. Examples of nitrile rubbers include acrylonitrile butadiene rubber and hydrogenated acrylonitrile butadiene rubber. Examples of cellulose derivatives include cellulose acetate, cellulose acetate butyrate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, or copolymers thereof. In addition, dispersants described in International Publication No. 2008 / 108360, JP 2018-192379 A, JP 2019-087304 A, Japanese Patent No. 6524479 A, and JP 2009-026744 A may be used, but are not limited to these.Particularly preferred are methyl cellulose, ethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, homopolymer of polyacrylonitrile, copolymer of polyacrylonitrile, and hydrogenated acrylonitrile butadiene rubber. Polymers in which other substituents have been introduced into a part of these polymers, modified polymers, etc. may also be used. The weight average molecular weight of the resin-type dispersant is preferably 500,000 or less, more preferably 300,000 or less, and more preferably 3,000 or more, and more preferably 5,000 or more, from the viewpoint of the balance of affinity between the dispersed substance and the dispersion medium and the resistance to the electrolyte. The resin-type dispersant may be used alone or in combination of two or more.
[0062] Commercially available polyvinyl alcohol resins are available in various grades under trade names such as Kuraray Poval (polyvinyl alcohol resin manufactured by Kuraray), Gohsenol, and Gohsenex (polyvinyl alcohol resin manufactured by Nippon Synthetic Chemical Industry Co., Ltd.). Modified polyvinyl alcohols having various functional groups are also available. Commercially available polyvinylpyrrolidone resins include, specifically, polyvinylpyrrolidone K30, K90 (manufactured by Fujifilm Wako), and K120 (manufactured by DSP Gokei Food & Chemical). Commercially available nitrile rubbers are available in various grades with different nitrile ratios, hydrogenation rates, and molecular weights under trade names such as Therban (hydrogenated nitrile rubber manufactured by Aranseo), Baymod (nitrile rubber manufactured by Aranseo), Zetpole (hydrogenated nitrile rubber manufactured by Nippon Zeon), and NipoleNBR (nitrile rubber manufactured by Nippon Zeon). Also, those synthesized by known synthesis methods may be used. Surfactants may be used in place of or in addition to the above-mentioned resin-type dispersants. Surfactants are classified into anionic, cationic, amphoteric ionic surfactants and nonionic surfactants.
[0063] The dispersant preferably contains a copolymer containing an aliphatic hydrocarbon structural unit and a nitrile group-containing structural unit, the aliphatic hydrocarbon structural unit contains an alkylene structural unit, the content of the aliphatic hydrocarbon structural unit is 40% by mass or more and less than 85% by mass based on the mass of the copolymer, and the content of the nitrile group-containing structural unit is 15% by mass or more and 50% by mass or less based on the mass of the copolymer. In this specification, this copolymer may be referred to as "copolymer I".
[0064] The aliphatic hydrocarbon structural unit is a structural unit containing an aliphatic hydrocarbon structure, and is preferably a structural unit consisting of only an aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure contains at least a saturated aliphatic hydrocarbon structure, and may further contain an unsaturated aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure preferably contains at least a linear aliphatic hydrocarbon structure, and may further contain a branched aliphatic hydrocarbon structure.
[0065] Examples of the aliphatic hydrocarbon structural unit include an alkylene structural unit, an alkenylene structural unit, an alkyl structural unit, an alkanetriyl structural unit, an alkanetetrayl structural unit, etc. The aliphatic hydrocarbon structural unit contains at least an alkylene structural unit.
[0066] The method for introducing an alkylene structural unit into the copolymer is not particularly limited, but examples thereof include the following method (1a) or (1b).
[0067] In the method (1a), a copolymer is prepared by polymerization reaction using a monomer composition containing a conjugated diene monomer. The prepared copolymer contains monomer units derived from the conjugated diene monomer. In the present invention, the "monomer units derived from the conjugated diene monomer" may be referred to as "conjugated diene monomer units", and the same may be omitted for monomer units derived from other monomers. Next, the conjugated diene monomer units are hydrogenated to convert at least a part of the conjugated diene monomer units into alkylene structural units. Hereinafter, "hydrogenation" may be referred to as "hydrogenation". The finally obtained copolymer contains units obtained by hydrogenating the conjugated diene monomer units as alkylene structural units.
[0068] In the method (1b), a copolymer is prepared by polymerization reaction using a monomer composition containing an α-olefin monomer. The prepared copolymer contains α-olefin monomer units. The finally obtained copolymer contains the α-olefin monomer units as alkylene structural units.
[0069] Among these, the method (1a) is preferred because the copolymer can be easily produced. The carbon number of the conjugated diene monomer is 4 or more, preferably 4 to 6. Examples of the conjugated diene monomer include conjugated diene compounds such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene. Among these, 1,3-butadiene is preferred. The alkylene structural unit preferably contains a structural unit (hydrogenated conjugated diene monomer unit) obtained by hydrogenating a conjugated diene monomer unit, and more preferably contains a structural unit (hydrogenated 1,3-butadiene monomer unit) obtained by hydrogenating a 1,3-butadiene monomer unit. The conjugated diene monomer may be used alone or in combination of two or more.
[0070] The hydrogenation is preferably carried out by a method capable of selectively hydrogenating the conjugated diene monomer units. Examples of the hydrogenation method include known methods such as oil phase hydrogenation and aqueous phase hydrogenation.
[0071] The hydrogenation can be carried out by a conventional method. For example, the hydrogenation can be carried out by treating a copolymer having conjugated diene monomer units dissolved in a suitable solvent with hydrogen gas in the presence of a hydrogenation catalyst. Examples of the hydrogenation catalyst include nickel, palladium, platinum, copper, etc.
[0072] In the method (1b), the carbon number of the α-olefin monomer is 2 or more, preferably 3 or more, and more preferably 4 or more. The carbon number of the α-olefin monomer is preferably 6 or less, and more preferably 5 or less. Examples of the α-olefin monomer include α-olefin compounds such as ethylene, propylene, 1-butene, and 1-hexene. The α-olefin monomer may be used alone or in combination of two or more.
[0073] In the aliphatic hydrocarbon structural unit, the content of the alkylene structural unit is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more, based on the total mass of the aliphatic hydrocarbon structural units (i.e., when the mass of the aliphatic hydrocarbon structural units is 100% by mass). The content of the alkylene structural unit is, based on the total mass of the aliphatic hydrocarbon structural units (i.e., when the mass of the aliphatic hydrocarbon structural units is 100% by mass), for example, less than 100% by mass, and may be 99.5% by mass or less, 99% by mass or less, or 98% by mass or less. The content of the alkylene structural unit may be 100% by mass.
[0074] The content of the aliphatic hydrocarbon structural unit is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more, based on the mass of the copolymer (i.e., when the mass of the copolymer is 100% by mass). The content of the aliphatic hydrocarbon structural unit is preferably less than 85% by mass, more preferably 75% by mass or less, and even more preferably 70% by mass or less, based on the mass of the copolymer (i.e., when the mass of the copolymer is 100% by mass).
[0075] The nitrile group-containing structural unit is a structural unit containing a nitrile group, preferably a structural unit containing an alkylene structure substituted with a nitrile group, more preferably a structural unit consisting of only an alkylene structure substituted with a nitrile group. The alkylene structure is preferably a linear or branched alkylene structure. The nitrile group-containing structural unit may further contain a structural unit containing (or consisting of) an alkyl structure substituted with a nitrile group. The number of nitrile groups contained in the nitrile group-containing structural unit is preferably one.
[0076] The method for introducing the nitrile group-containing structural unit into the copolymer is not particularly limited, but a method (method (2a)) of preparing a copolymer by polymerization reaction using a monomer composition containing a nitrile group-containing monomer can be preferably used. The finally obtained copolymer contains the nitrile group-containing monomer unit as a nitrile group-containing structural unit. Examples of the nitrile group-containing monomer capable of forming the nitrile group-containing structural unit include monomers containing a polymerizable carbon-carbon double bond and a nitrile group. For example, an α,β-ethylenically unsaturated group-containing compound having a nitrile group can be mentioned, and specifically, acrylonitrile, methacrylonitrile, etc. can be mentioned. In particular, from the viewpoint of increasing the adsorption force between the copolymers and / or between the copolymer and the fibrous carbon, it is preferable that the nitrile group-containing monomer contains acrylonitrile. The nitrile group-containing monomer can be used alone or in combination of two or more kinds.
[0077] The content of the nitrile group-containing structural unit is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, based on the mass of the copolymer (i.e., when the mass of the copolymer I is 100% by mass). The content of the nitrile group-containing structural unit is preferably 50% by mass or less, more preferably 46% by mass or less, and even more preferably 40% by mass or less, based on the mass of the copolymer (i.e., when the mass of the copolymer is 100% by mass). By setting the content of the nitrile group-containing structural unit within the above range, the adsorption to the fibrous carbon can be controlled. In addition, the affinity of the copolymer to the electrolyte can be controlled, and problems such as the copolymer dissolving in the electrolyte in the battery and increasing the resistance of the electrolyte can be prevented.
[0078] The amide group-containing structural unit is a structural unit containing an amide group, preferably a structural unit containing an alkylene structure substituted with an amide group, more preferably a structural unit consisting of only an alkylene structure substituted with an amide group. The alkylene structure is preferably a linear or branched alkylene structure. The amide group-containing structural unit may further contain a structural unit containing (or consisting of) an alkyl structure substituted with an amide group. The number of amide groups contained in the amide group-containing structural unit is preferably one. The amide group is a substituted or unsubstituted carbamoyl group, and examples of the substituent include an alkyl group and a hydroxyalkyl group. By including an amide group-containing structural unit in the copolymer, the adsorptivity to fibrous carbon or an electrode active material is significantly improved, and the rate characteristics and cycle characteristics are improved. In the present specification, a "substituted or unsubstituted carbamoyl group" (-CO-NR'2 (R' is each independently a hydrogen atom or a substituent)) may be referred to as an "amide group".
[0079] The method for introducing an amide group-containing structural unit into the copolymer is not particularly limited, but examples thereof include the following method (3a) or (3b).
[0080] In the method (3a), a copolymer is prepared by polymerization reaction using a monomer composition containing an amide group-containing monomer. The prepared copolymer contains amide group-containing monomer units. The final copolymer contains the amide group-containing monomer units as amide group-containing structural units.
[0081] In the method (3b), a copolymer containing a nitrile group-containing structural unit is prepared, and then, the nitrile groups contained in the nitrile group-containing structural unit are hydrolyzed in a basic atmosphere to convert at least a part of the nitrile group-containing structural unit into an amide group-containing structural unit.
[0082] When the copolymer is prepared via the method (3b), the introduction of amide groups into the copolymer can be confirmed by NMR (nuclear magnetic resonance) and / or IR (infrared spectroscopy) measurements. In addition, it can be confirmed simply by the change in weight average molecular weight and / or viscosity (solution viscosity) that occurs between the copolymer before hydrolysis and the copolymer. The weight average molecular weight of the copolymer tends to be smaller than the weight average molecular weight of the copolymer before hydrolysis (for example, 0.05 to 0.6 times). In addition, for example, the viscosity of the copolymer solution at a shear stress of 1,000 / s tends to be smaller than the viscosity of the copolymer solution at a shear stress of 1,000 / s before hydrolysis (for example, 0.05 to 0.6 times). It should be noted that, regardless of the preparation method of the copolymer, the introduction of amide groups into the copolymer can be confirmed by NMR (nuclear magnetic resonance) and / or IR (infrared spectroscopy) measurements.
[0083] In the method (3a), examples of the amide group-containing monomer include monoalkyl (meth)acrylamides such as (meth)acrylamide, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, and N-isopropyl (meth)acrylamide; dialkyl (meth)acrylamides such as N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide; N-(hydroxyalkyl) (meth)acrylamides such as N-(2-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, and N-(2-hydroxybutyl) (meth)acrylamide; diacetone (meth)acrylamide; and acryloylmorpholine. In this specification, "(meth)acryl" refers to acryl or methacryl. In particular, the amide group-containing monomer preferably includes at least one selected from the group consisting of acrylamide, methacrylamide, and N,N-dimethylacrylamide. The amide group-containing monomers can be used alone or in combination of two or more.
[0084] In the method (3b), in order to create a basic atmosphere, at least one base selected from the group consisting of inorganic bases and organic hydroxides (organic bases) can be used.
[0085] Examples of inorganic bases include chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, tungstates, vanadates, molybdates, niobates, or borates of alkali metals or alkaline earth metals; and ammonium hydroxide. Among these, hydroxides of alkali metals or alkaline earth metals are preferred from the viewpoint of easily supplying cations. Examples of hydroxides of alkali metals include lithium hydroxide, sodium hydroxide, potassium hydroxide, and the like. Examples of hydroxides of alkaline earth metals include calcium hydroxide, magnesium hydroxide, and the like. Among these, it is more preferable to use at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, and potassium hydroxide. The metal contained in the inorganic base may be a transition metal.
[0086] The organic hydroxide is a salt containing an organic cation and a hydroxide ion. Examples of the organic hydroxide include trimethyl-2-hydroxyethyl ammonium hydroxide, tetramethyl ammonium hydroxide, cetyl trimethyl ammonium hydroxide, hexadecyl trimethyl ammonium hydroxide, trimethyl phenyl ammonium hydroxide, 3-trifluoromethyl-phenyl trimethyl ammonium hydroxide, and benzyl trimethyl ammonium hydroxide. Among these, it is particularly preferable to use at least one selected from the group consisting of trimethyl-2-hydroxyethyl ammonium hydroxide and tetramethyl ammonium hydroxide.
[0087] The amount of the base used is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, based on the mass of the copolymer. The amount of the base used is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, based on the mass of the copolymer. If the amount used is too small, the denaturation of the nitrile group by hydrolysis tends not to occur easily. If the amount used is too large, it may cause corrosion of the dispersion device and / or the inside of the battery.
[0088] In the method (3b), hydrolysis can be carried out by mixing a copolymer containing an alkylene structural unit and a nitrile group-containing monomer unit, a base, and a solvent. Any other components may be mixed. There is no limitation on the order of addition of the copolymer, the base, and the solvent to the container and the mixing method, and they may be added to the container at the same time; the copolymer, the base, and the solvent may be added separately to the container; or one or both of the copolymer and the base may be mixed with the solvent to prepare a copolymer-containing liquid and / or a base-containing liquid, and the copolymer-containing liquid and / or the base-containing liquid may be added to the container. In particular, since the nitrile group can be efficiently modified, a method in which a base dispersion in which a base is dispersed in a solvent is added to a copolymer solution in which the copolymer is dissolved in a solvent while stirring is preferred. A disperser (dispersing machine) or a homogenizer can be used for stirring. As the solvent, the solvents listed in the description of the dispersant composition described later can be used.
[0089] The content of the amide group-containing structural unit is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, and particularly preferably 1% by mass or less, based on the mass of the copolymer (i.e., when the mass of the copolymer is 100% by mass). When the content of the amide group-containing structural unit is below the above range, the problem of gelation of the fibrous carbon dispersion during storage, which may occur due to the hydrogen bonds between the copolymers being too strong, can be prevented. The content of the amide group-containing structural unit is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, even more preferably 0.5% by mass or more, and particularly preferably 0.7% by mass or more, based on the mass of the copolymer (i.e., when the mass of the copolymer is 100% by mass). When the content of the amide group-containing structural unit is above the above range, the adsorption force to the fibrous carbon, which is the dispersed material, can be sufficiently improved to obtain the effect.
[0090] Preferred embodiments of the copolymer include the following. A copolymer in which the total content of aliphatic hydrocarbon structural units, nitrile group-containing structural units, and carbamoyl group-containing structural units is 80% by mass or more and 100% by mass or less based on the mass of the copolymer. The total content is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more. A copolymer in which the total content of aliphatic hydrocarbon structural units, nitrile group-containing structural units, and carbamoyl group-containing structural units contained therein is 80% by mass or more and 100% by mass or less based on the mass of the copolymer. The total content is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more.
[0091] In this specification, the content of the structural unit can be determined by utilizing the amount of monomer used, NMR (nuclear magnetic resonance) and / or IR (infrared spectroscopy) measurement.
[0092] A preferred embodiment of the method for producing the copolymer is as follows. A method for producing a copolymer, comprising: preparing a copolymer by polymerization reaction using a monomer composition containing a conjugated diene monomer and a nitrile group-containing monomer (methods (1a) and (2a)); hydrogenating a conjugated diene monomer unit contained in the copolymer (method (1a)); and modifying a nitrile group-containing structural unit contained in the copolymer by hydrolysis (method (3b)). In this method, some or all of the conjugated diene monomer units are hydrogenated, and some (but not all) of the nitrile group-containing structural units are modified by hydrolysis so that the copolymer contains nitrile group-containing structural units. A method for producing a copolymer, comprising: preparing a copolymer by polymerization reaction using a monomer composition containing a conjugated diene monomer, a nitrile group-containing monomer, and an amide group-containing monomer (methods (1a), (2a), and (3a)); and hydrogenating the conjugated diene monomer units contained in the copolymer (method (1a)). In this method, a part or all of the conjugated diene monomer units are hydrogenated.
[0093] The polymerization reaction used for preparing the copolymer is preferably an emulsion polymerization reaction, and a conventional emulsion polymerization method can be used. Polymerization agents such as emulsifiers (surfactants), polymerization initiators, chelating agents, oxygen scavengers, and molecular weight regulators used in emulsion polymerization can be any conventionally known agent, and are not particularly limited. For example, anionic emulsifiers or anionic and nonionic emulsifiers are usually used as emulsifiers.
[0094] Examples of the anionic emulsifier include fatty acid salts such as potassium tallow fatty acid, partially hydrogenated potassium tallow fatty acid, potassium oleate, and sodium oleate; resin acid salts such as potassium rosinate, sodium rosinate, potassium hydrogenated rosinate, and sodium hydrogenated rosinate; and alkylbenzene sulfonate salts such as sodium dodecylbenzene sulfonate. Examples of the nonionic emulsifier include emulsifiers of polyethylene glycol ester type, polypropylene glycol ester type, and block copolymer type of ethylene oxide and propylene oxide.
[0095] Examples of the polymerization initiator include thermal decomposition initiators such as persulfates, such as potassium persulfate and ammonium persulfate; organic peroxides, such as t-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, octanoyl peroxide, and 3,5,5-trimethylhexanoyl peroxide; azo compounds, such as azobisisobutyronitrile; and redox initiators consisting of these and a reducing agent, such as divalent iron ions. Among these, redox initiators are preferred. The amount of the initiator used is, for example, in the range of 0.01 to 10% by mass with respect to the total amount of the monomers.
[0096] The emulsion polymerization reaction may be either a continuous or batch type. The polymerization temperature may be either low-temperature or high-temperature polymerization, but is preferably 0 to 50°C, more preferably 0 to 35°C. The method of adding the monomer (lump addition, divided addition, etc.), the polymerization time, the polymerization conversion rate, etc. are not particularly limited. The conversion rate is preferably 85% by mass or more, more preferably 90% by mass or more.
[0097] The weight average molecular weight of the copolymer is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 50,000 or more. The weight average molecular weight of the copolymer is preferably 400,000 or less, more preferably 350,000 or less, and even more preferably 300,000 or less. When the weight average molecular weight of the copolymer is 5,000 or more and 400,000 or less, the adsorption to the dispersed material and the affinity to the dispersion medium become good, and the stability of the dispersion tends to be improved. The weight average molecular weight is a weight average molecular weight in terms of polystyrene, and can be measured by gel permeation chromatography (GPC). Specifically, it may be measured by the method described in the examples.
[0098] The dispersant contains at least a copolymer. The dispersant may further contain any polymer, any copolymer, etc. The content of the copolymer in the dispersant is preferably 50% by mass or more, more preferably 80% by mass or more, and more preferably 90% by mass or more. The content of the copolymer in the dispersant may be 100% by mass, in which case the dispersant consists of only the copolymer.
[0099] It is preferable to add a base to the resin composition, since it enhances the wettability of the fibrous carbon in the dispersion medium, improves the dispersibility, and improves the dispersion stability. The base to be added may be at least one selected from the group consisting of inorganic bases, inorganic metal salts, organic bases, and organic metal salts.
[0100] Examples of inorganic bases and inorganic metal salts include chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, tungstates, vanadates, molybdates, niobates, borates, and ammonium hydroxides of alkali metals or alkaline earth metals. Among these, hydroxides or alkoxides of alkali metals or alkaline earth metals are preferred from the viewpoint of easily supplying cations. Examples of hydroxides of alkali metals include lithium hydroxide, sodium hydroxide, potassium hydroxide, and the like. Examples of hydroxides of alkaline earth metals include calcium hydroxide, magnesium hydroxide, and the like. Among these, it is more preferable to use at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, and potassium hydroxide. The metal contained in the inorganic base may be a transition metal.
[0101] Examples of the organic base include primary, secondary and tertiary amine compounds having 1 to 40 carbon atoms (eg, alkylamines and amino alcohols) which may have a substituent, and organic hydroxides.
[0102] Examples of organic metal salts include alkoxides of alkali metals and acetates of alkali metals. Examples of alkoxides of alkali metals include lithium methoxide, lithium ethoxide, lithium propoxide, lithium t-butoxide, lithium n-butoxide, sodium methoxide, sodium ethoxide, sodium propoxide, sodium t-butoxide, sodium n-butoxide, potassium methoxide, potassium ethoxide, potassium propoxide, potassium t-butoxide, and potassium n-butoxide. Among these, sodium t-butoxide is preferred from the viewpoint of easily supplying cations. The metal of the inorganic base may be a transition metal.
[0103] The amount of the base used is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, based on the mass of the polymer. The amount of the base used is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, based on the mass of the polymer. If the amount used is too small, the decrease in Mooney viscosity tends not to occur easily. If the amount used is too large, it may cause corrosion of the dispersion device and / or the inside of the battery.
[0104] In addition to the above-mentioned dispersant, the fibrous carbon dispersion may further contain an inorganic base, an inorganic metal salt, an organic base, an organic metal salt, or a combination thereof. The total amount of these is preferably 0.001 to 0.1 mass%, more preferably 0.005 to 0.05 mass%, based on the total amount of the resin composition.
[0105] <Solvent (dispersion medium)> The dispersion medium of the fibrous carbon dispersion is not particularly limited, but is preferably a high dielectric constant solvent, and preferably contains one of the high dielectric constant solvents or a mixed solvent of two or more of them. In addition, the high dielectric constant solvent may be mixed with one or more other solvents.
[0106] Examples of high dielectric constant solvents that can be used include amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.), heterocyclics (cyclohexylpyrrolidone, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, etc.), sulfoxides (dimethyl sulfoxide, etc.), sulfones (hexamethylphosphorotriamide, sulfolane, etc.), lower ketones (acetone, methyl ethyl ketone, etc.), carbonates (diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate), water, and others such as tetrahydrofuran, urea, and acetonitrile. The dispersion medium preferably contains an amide-based organic solvent or water, and the amide-based organic solvent more preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone. The relative dielectric constant of the high dielectric constant solvent can be a value listed in the Solvent Handbook, etc., and is preferably 2.5 or more at 20°C.
[0107] <Slurry for secondary battery electrode composite material> A slurry for a secondary battery electrode can be prepared using the composite for a secondary battery electrode. A composite slurry for a secondary battery electrode can be obtained by adding the composite for an electrode and a binder resin to a dispersion medium. If necessary, a fibrous carbon dispersion and other optional components may be appropriately contained within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the composite slurry, during mixing, after mixing, or a combination thereof. The optional components may be those described above for the fibrous carbon dispersion. The active material may be a positive electrode active material or a negative electrode active material. In this specification, the positive electrode active material and the negative electrode active material may be simply referred to as "active material".
[0108] The solid content in the composite slurry is preferably 30% by mass or more, and more preferably 40% by mass or more, based on the mass of the composite slurry (the mass of the composite slurry being 100% by mass), and is preferably 90% by mass or less, and more preferably 85% by mass or less.
[0109] The content of the electrode composite in the composite slurry is preferably 28% by mass or more, more preferably 38% by mass or more, and even more preferably 48% by mass or more, based on the mass of the composite slurry (the mass of the composite slurry being 100% by mass), and is preferably 88% by mass or less, and more preferably 80% by mass or less.
[0110] The content of the binder resin in the composite slurry is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass). Also, it is preferably 20% by mass or less, more preferably 10% by mass or less. When the electrode composite contains a binder resin, it is preferable to adjust the total amount of the binder resin in the composite slurry to be within the above range.
[0111] The content of fibrous carbon in the composite slurry is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.05% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass). Also, it is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and even more preferably 3% by mass or less. Since the electrode composite of the present invention contains fibrous carbon, it is preferable to adjust the total amount of fibrous carbon in the composite slurry to be within the above range. If it exceeds the above range, the filling amount of the active material in the electrode decreases, resulting in a low capacity of the battery. Also, if it is below the above range, the conductivity of the electrode and the battery may be insufficient.
[0112] <Method for producing secondary battery electrode composite slurry>
[0113] In the method for preparing the composite slurry, the order of adding the electrode composite and the binder resin to the dispersion medium is not particularly limited. For example, a method of preparing the binder resin by adding the binder resin to the dispersion medium to prepare a binder resin composition, and then adding the electrode composite to the binder resin composition; a method of preparing the electrode composite by adding the binder resin to the dispersion medium and then adding the binder resin; a method of preparing the binder resin and the electrode composite by adding them all at once to the dispersion medium, and the like can be mentioned. As a method for preparing the composite slurry, a method of adding the binder resin to the dispersion medium to prepare a binder resin composition, and then adding the electrode composite to the binder resin composition and performing a stirring process is preferable. The stirring device used for stirring is not particularly limited. A disperser, a homogenizer, etc. can be used as the stirring device.
[0114] <Electrode for secondary batteries> The secondary battery electrode in the present invention includes a composite for secondary battery electrodes. The electrode may further include an optional component such as a dispersant. The electrode may be formed by preparing the above-mentioned composite slurry and applying the composite slurry, or by adding a binder or the like to the composite for secondary battery electrodes without using the composite slurry and forming each component into a sheet by pressing or the like. When the composite slurry is not used, a dry mixture that has been mixed in advance or a dried product after wet mixing may be used. When the composite slurry is used, for example, the electrode film can be formed by applying the composite slurry to a current collector and removing volatiles.
[0115] <Method of manufacturing secondary battery electrodes> The material and shape of the current collector are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the current collector can be metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil, or a mesh-shaped current collector can also be used. The thickness of the current collector is preferably about 0.5 to 30 μm.
[0116] The method of applying the composite slurry onto the current collector is not particularly limited, and any known method can be used.Specific examples include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting.As a drying method after application, standing drying, a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, and the like can be used, but are not particularly limited thereto.
[0117] The method for dry-mixing or wet-mixing each component by adding a binder or the like to the composite for secondary battery electrode without using a composite slurry is not particularly limited, and any known method can be used. Specifically, a dry / wet disperser described in the composite preparation method can be appropriately selected.
[0118] After the composite slurry is applied, it may be rolled using a lithographic press, a calendar roll, etc. The thickness of the electrode film is, for example, 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.
[0119] When forming an electrode by adding a binder or the like to a composite for a secondary battery electrode and pressing each component into a sheet without using a composite slurry, each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be directly supplied to a current collector and pressure-molded, or a free-standing film made of each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be prepared in advance and then laminated on a current collector. Also, a thin resin film serving as a binder component may be formed on the current collector in advance.
[0120] Examples of the method for pressure molding include a planographic press, a calendar roll, etc. Among them, the use of a calendar roll is preferred because of its productivity and ability to produce uniform molding.
[0121] <Secondary battery> The secondary battery includes a positive electrode, a negative electrode, and an electrolyte, and at least one selected from the group consisting of the positive electrode and the negative electrode includes an electrode film made from the composite of the present invention.
[0122] The positive electrode may be formed by forming an electrode film containing a positive electrode active material on a current collector, and the negative electrode may be formed by forming an electrode film containing a negative electrode active material on a current collector.
[0123] The electrolyte may be any of a liquid electrolyte, a gel electrolyte, and a solid electrolyte. For example, the liquid electrolyte may contain an electrolyte salt such as a lithium salt and a non-aqueous solvent. As the electrolyte salt, various conventionally known electrolytes capable of moving ions can be used. For example, lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be used, but are not limited thereto. The electrolyte salt is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.
[0124] The non-aqueous solvent is not particularly limited, but examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.
[0125] The secondary battery preferably includes a separator, such as, but not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics obtained by subjecting these to hydrophilic treatment.
[0126] The structure of the secondary battery is not particularly limited, but typically includes a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes depending on the purpose of use, such as a paper type, a cylindrical type, a button type, or a laminated type.
[0127] The composite for secondary battery electrodes of the present invention is an ideal composite of active material and fibrous carbon, and therefore can be suitably used not only for electrodes made from composite slurries, but also for electrodes made by solid or semi-solid processes. Electrodes made by these solid processes can be applied not only to lithium ion secondary batteries using conventional electrolytes, but also to all-solid batteries and semi-solid batteries.
[0128] The secondary battery of the present invention can be suitably used as a battery for vehicles such as automobiles, and portable electronic devices such as personal computers and smartphones. EXAMPLES
[0129] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0130] <Preparation of sample for weight average molecular weight (Mw) measurement> The copolymer was separated and collected from a dispersant-containing liquid (dispersant composition) containing a copolymer, a base, and a solvent by the following method, and used as a measurement sample. The dispersant-containing liquid was dropped into purified water to precipitate the copolymer, and the precipitate was collected by filtering through a Buchner funnel. The precipitate was rinsed by sprinkling purified water on the Buchner funnel as it was, and then dissolved in tetrahydrofuran (THF) to obtain a solution. The obtained solution was dropped again into purified water to perform the filtration and washing steps using purified water, and the precipitate was redissolved in THF to obtain a measurement sample. In addition, the conductive material was separated from the conductive material dispersion containing the copolymer, base, solvent, and conductive material by centrifugation, and the same steps as above were performed on the separated supernatant to prepare a measurement sample.
[0131] <Measurement of weight average molecular weight (Mw)> The weight average molecular weight (Mw) of the copolymer was measured by gel permeation chromatography (GPC) equipped with an RI detector. The apparatus used was HLC-8320GPC (manufactured by Tosoh Corporation), and three separation columns were connected in series. The packing materials were "TSK-GEL SUPER AW-4000", "AW-3000", and "AW-2500" manufactured by Tosoh Corporation, respectively. The oven temperature was 40°C, and an N,N-dimethylformamide solution of 30 mM triethylamine and 10 mM LiBr was used as the eluent, and the measurement was performed at a flow rate of 0.6 mL / min. The concentration of the measurement sample was adjusted to 1% using a solvent consisting of the eluent, and 20 microliters were injected. The weight average molecular weight is a polystyrene equivalent value.
[0132] <Infrared spectroscopic analysis using total reflectance measurement method> The solid copolymer was used as it was for the measurement. The dispersant-containing liquid (dispersant composition) was treated with hot air at 100°C for 10 hours to thoroughly dry and solidify, and the obtained solid copolymer was used as the measurement sample. The measurement sample was subjected to IR measurement using an infrared spectrophotometer (Nicolet iS5 FT-IR spectrometer manufactured by Thermo Fisher Scientific Co., Ltd.).
[0133] <Measurement of hydrogenation rate of copolymer> The hydrogenation rate was determined by IR measurement in the same manner as the infrared spectroscopy analysis by the total reflection measurement method described above. The double bond derived from the conjugated diene monomer unit has a peak at 970 cm-1, and the hydrogenated single bond has a peak at 723 cm-1. The hydrogenation rate was calculated from the ratio of the heights of these two peaks.
[0134] <Measurement of Amide Group-Containing Structural Unit Content> The content of the amide group-containing structural unit in the copolymer introduced by hydrolysis of the nitrile group-containing structural unit was measured by a nuclear magnetic resonance apparatus (ADVANCE400 Nanobay: manufactured by Bruker Japan Co., Ltd., using a measurement solvent of CDCl3 and a 10 mm NMR tube). 1 3 The modification rate (molar ratio) of the nitrile group was calculated from the C-NMR quantitative spectrum using the formula [A] / ([A]+[B]) and converted into the composition ratio (mass%) in the entire copolymer. In the table below, "amide group amount" means "content (mass%) of amide group-containing structural unit." [A]: Peak area at chemical shift values of 180.5 to 183.5 ppm [B]: Peak area at chemical shift values of 121.5 to 123.0 ppm However, because the quantitative sensitivity of 13C-NMR measurement is low, it cannot detect the amide group-containing structural unit unless the content is 1% or more. Therefore, the amide group-derived peak at about 1570 cm was detected by IR measurement in the same manner as the infrared spectroscopy using the total reflection measurement method described above. - 1 and about 1650 cm - 1 Copolymers in which a peak could be detected were judged to contain amide group-containing structural units, and the content of amide group-containing structural units was determined to be less than 1%. In addition, since a peak could be detected by the same IR measurement as above, the content of amide group-containing structural units was judged to be 0.3% or more. In addition, when the amide group-containing structural unit is introduced through a method of preparing a copolymer using a monomer composition containing an amide group-containing monomer, the content of the amide group-containing structural unit is also considered to be less than 1%, since it is also impossible to quantify if it is less than 1%. 1 3The ratio of the nitrile group-containing structural unit to the amide group-containing structural unit was confirmed by C-NMR quantitative spectrum, and it was confirmed that for copolymers having an amide group-containing structural unit content of 1% or more, the content coincided with the content calculated from the amount of monomer charged during synthesis.
[0135] <Production of Dispersant> (Dispersant 1: Production of Polyacrylonitrile (PAN)) A reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer was charged with 100 parts of acetonitrile and substituted with nitrogen gas. The reaction vessel was heated to 70°C, and a mixture of 90.0 parts of acrylonitrile, 10.0 parts of hydroxyethyl acrylate, and 5.0 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (NOF Corp.; V-65) was added dropwise over 3 hours to carry out a polymerization reaction. After completion of the dropwise addition, the reaction was continued for another hour at 70°C, and then 0.5 parts of Perbutyl O was added, and the reaction was continued for another hour at 70°C. Thereafter, the conversion rate was confirmed to exceed 98% by measuring the nonvolatile content, and the dispersion medium was completely removed by vacuum concentration to obtain a dispersant (polyacrylonitrile). The weight average molecular weight (Mw) of polyacrylonitrile was 15,000.
[0136] (Dispersant 2 H-NBR production) In a stainless steel polymerization reactor, 30 parts of acrylonitrile, 70 parts of 1,3-butadiene, 3 parts of potassium soap oleate, 0.3 parts of azobisisobutyronitrile, 0.48 parts of t-dodecyl mercaptan, and 200 parts of ion-exchanged water were added. Under a nitrogen atmosphere, polymerization was carried out at 45°C for 20 hours while stirring, and the polymerization was terminated at a conversion rate of 90%. Unreacted monomers were removed by vacuum stripping to obtain an acrylonitrile-conjugated diene rubber latex with a solid content concentration of about 30%. Subsequently, ion-exchanged water was added to the latex to adjust the total solid content concentration to 12%, and the latex was placed in a 1L autoclave equipped with a stirrer, and nitrogen gas was passed through for 10 minutes to remove dissolved oxygen in the contents. A catalyst solution prepared by dissolving 75 mg of palladium acetate as a hydrogenation catalyst in 180 mL of ion-exchanged water to which nitric acid was added in an amount four times the moles of palladium was added was added to the autoclave. After replacing the inside of the autoclave with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to 3 MPa, and hydrogenation reaction was carried out for 6 hours. Thereafter, the contents were returned to room temperature, the inside of the autoclave was made into a nitrogen atmosphere, and the solid content was dried to obtain dispersant 2. The hydrogenation rate (calculated from infrared spectroscopy analysis by total reflection measurement method) was 99%. The weight average molecular weight (Mw) was 200,000. In the acrylonitrile-conjugated diene rubber, the content of the conjugated diene monomer unit was 70% and the content of the nitrile group-containing monomer unit was 30% based on the mass of the acrylonitrile-conjugated diene rubber. In the copolymer, the content of the aliphatic hydrocarbon structural unit containing an alkylene structural unit was 70% and the content of the nitrile group-containing monomer unit was 30% based on the mass of the copolymer. The contents of these monomer units and structural units were determined from the amounts of the monomers used (hereinafter the same applies).
[0137] (Manufacture of dispersant 3H-NBR) In a stainless steel polymerization reactor, 49 parts of acrylonitrile, 51 parts of 1,3-butadiene, 3 parts of potassium soap oleate, 0.3 parts of azobisisobutyronitrile, 0.48 parts of t-dodecyl mercaptan, and 200 parts of ion-exchanged water were added. Under a nitrogen atmosphere, polymerization was carried out at 45°C for 20 hours while stirring, and the polymerization was terminated at a conversion rate of 90%. Unreacted monomers were removed by vacuum stripping to obtain an acrylonitrile-conjugated diene rubber latex with a solid content concentration of about 30%. Subsequently, ion-exchanged water was added to the latex to adjust the total solid content concentration to 12%, and the latex was placed in a 1L autoclave equipped with a stirrer, and nitrogen gas was passed through it for 10 minutes to remove dissolved oxygen in the contents. A catalyst solution prepared by dissolving 75 mg of palladium acetate as a hydrogenation catalyst in 180 mL of ion-exchanged water to which nitric acid was added in an amount four times the moles of palladium was added was added to the autoclave. After replacing the inside of the autoclave with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to 3 MPa, and hydrogenation reaction was carried out for 6 hours. Thereafter, the contents were returned to room temperature, the inside of the autoclave was made into a nitrogen atmosphere, and the solid content was dried to obtain dispersant 3. In addition, the hydrogenation rate (calculated from infrared spectroscopy analysis by total reflection measurement method) was 99%. The weight average molecular weight (Mw) of dispersant 3 was 200,000. The content of nitrile group-containing structural units was 49%, and the content of aliphatic hydrocarbon structural units was 51%.
[0138] (Dispersant 4: Production of amidated H-NBR) In a stainless steel container 1, 16 parts of NaOH and 84 parts of NMP were placed, and the mixture was stirred with a homogenizer for 1 hour to prepare a suspension of NaOH. In a stainless steel container 2, 9 parts of dispersant 2 and 91 parts of NMP were placed, and the mixture was stirred with a homogenizer for 1 hour to prepare a solution of dispersant 2. Next, 3.8 parts of the suspension of NaOH and 96.2 parts of the solution of dispersant 2 were placed in a stainless steel container 3, and NMP was further added to adjust the concentration to obtain a mixture. The water content of the mixture was 0.1%. The mixture was stirred with a homogenizer for 2 hours to modify a part of the nitrile group of dispersant 2 to an amide group, and a copolymer as dispersant 4 (in the examples, the modified copolymer may be referred to as "dispersant 4"), NMP, and a dispersant 4-containing liquid (dispersant composition) containing NaOH was obtained. The weight average molecular weight (Mw) of dispersant 4 was 50,000. In Dispersant 4, the content of aliphatic hydrocarbon structural units including alkylene structural units was 70%, the content of nitrile group-containing monomer units was more than 29% and less than 30%, and the content of amide group-containing structural units was less than 1%, based on the mass of Dispersant 4. The contents of these structural units were determined using the amounts of monomers used, NMR (nuclear magnetic resonance) and / or IR (infrared spectroscopy) measurements (the same applies below).
[0139] (Dispersant 5: Production of amidated H-NBR) A dispersant 5-containing liquid (dispersant composition) containing a copolymer as dispersant 5 (in the examples, the copolymer after modification may be referred to as "dispersant 5"), NMP, and NaOH was obtained in the same manner as in the production method of dispersant 4, except that 9 parts of dispersant 3 were added to the stainless steel container 2. The weight average molecular weight (Mw) of dispersant 5 was 50,000. In dispersant 5, based on the mass of dispersant 5, the content of aliphatic hydrocarbon structural units including alkylene structural units was 70%, the content of nitrile group-containing monomer units was more than 29% and less than 30%, and the content of amide group-containing structural units was less than 1%.
[0140] (Dispersant 6: Production of amidated H-NBR) The amount of NaOH suspension was changed to 74.6 parts and the amount of dispersant 2 solution was changed to 25.4 parts, and the amount of dispersant 2 was changed to 74.6 parts and 25.4 parts, and the amount of dispersant 2 solution was changed to 25.4 parts and charged into the stainless steel container 3. The procedure was the same as that for dispersant 4, and a dispersant 6-containing liquid (dispersant composition) containing a copolymer as dispersant 6 (in the examples, the copolymer after modification may be referred to as "dispersant 6"), NMP, and NaOH was obtained. The weight average molecular weight (Mw) of dispersant 6 was 25,000. In dispersant 6, the content of aliphatic hydrocarbon structural units containing alkylene structural units was 70%, the content of nitrile group-containing monomer units was 26%, and the content of amide group-containing structural units was 2%, based on the mass of dispersant 6.
[0141] In addition, the following dispersants were used in the examples and comparative examples. PVP: Polyvinylpyrrolidone (K-30, Fujifilm Wako Pure Chemical Industries, Ltd.) PVA: Polyvinyl alcohol (Poval 203 manufactured by Kuraray)
[0142] In the examples and comparative examples, the following fibrous carbon was used. 100T: K-Nanos-100T (KUMHO PETROCHEMICAL, multi-walled CNT, fiber diameter 13.7 nm)
[0143] In the examples and comparative examples, the following active materials were used. NMC111: NMC111 (LiNi 0.33 Mn 0.33 Co 0.33 O2, Sigma-Aldrich)
[0144] <Preparation of fibrous carbon dispersion> (Production Example 1) According to the materials and compositions shown in Table 1, a fibrous carbon dispersion was prepared as follows. First, NMP was placed in a stainless steel container and heated to 50°C. A dispersant was added while stirring with a disperser, and then the mixture was stirred for 1 hour to dissolve the dispersant. Next, fibrous carbon was added while stirring with a disperser, and a square-hole high shear screen was attached to a high shear mixer (L5M-A, manufactured by SILVERSON). Batch dispersion was performed at a speed of 8,000 rpm until the entire mixture became uniform and the dispersion particle size was 250 μm or less using a grind gauge with a maximum groove depth of 300 μm. At this time, the dispersion particle size confirmed by the grind gauge was 220 μm. Next, the liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and a circulation-type dispersion process was performed. The dispersion process was performed using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa. The dispersion liquid was dispersed until the viscosity at 60 rpm measured with a B-type viscometer (TOKISANGYO, VISCOMETER, MODEL: BL) was 3,000 mPa·s or less. After that, the dispersion was subjected to 20 passes of dispersion processing with a high-pressure homogenizer to obtain fibrous carbon dispersion 1.
[0145] (Examples 2 to 9) Fibrous carbon dispersions 2 to 9 were obtained in the same manner as in Production Example 1, except that the materials and compositions were changed according to Table 1.
[0146] [Table 1] NaOH: Sodium hydroxide (Tokyo Chemical Industry Co., Ltd., purity >98.0%, granular)
[0147] <Electrode composite for secondary batteries> (Example 1-1) According to the composition shown in Table 2, a mixture of NMC and fibrous carbon dispersion 1 was prepared by stirring at a rotation speed of 4000 rpm for 10 minutes using a high-shear multi-function machine Mechanofusion manufactured by Hosokawa Micron Corporation. After that, it was dried at 120°C for 2 hours in a hot air oven to obtain composite 1.
[0148] (Examples 1-2 to 11) According to the compositions shown in Table 2, Composites 2 to 11 were obtained in the same manner as in Example 1-1.
[0149] (Examples 1 to 12) According to the composition shown in Table 2, NMC and fibrous carbon dispersion 1 were mixed using a planetary mixer at a rotation speed of 30 rpm for 60 minutes to prepare a mixture. After that, the mixture was dried at 120°C for 2 hours in a hot air oven to obtain composite 12.
[0150] (Examples 1-13 to 1-22) Composites 13 to 22 were obtained in the same manner as in Examples 1 to 12 according to the compositions shown in Table 2.
[0151] (Examples 1-23) According to the composition shown in Table 2, NMC, fibrous carbon dispersion 5, and 8% binder solution (polyvinylidene fluoride resin: W#9300) were added using a planetary mixer and stirred for 60 minutes at a rotation speed of 50 rpm to produce a mixture. After that, the mixture was dried at 120°C for 2 hours in a hot air oven to obtain composite 23.
[0152] (Examples 1-24) A composite for secondary battery electrodes was prepared using a high-speed mixer made by EarthTechnica Corporation according to the composition shown in Table 2. NMC and fibrous carbon dispersion 5 were stirred at an agitator rotation speed of 500 rpm and a chopper rotation speed of 1500 rpm, and then dried in an oven at 120°C for 2 hours to obtain composite 24.
[0153] (Examples 1-25) According to the composition shown in Table 2, the fibrous carbon dispersion 5 and the solvent (NMP) were weighed out and placed in a stainless steel container, and NMC was added while stirring with a disperser, and then the mixture was stirred for 60 minutes to obtain a slurry. The slurry was used to prepare a composite for secondary battery electrodes using a spray dryer, Mini Spray Dryer B-290, manufactured by Nippon Buchi Co., Ltd. The slurry was spray-dried at 220°C under closed system conditions (nitrogen atmosphere) using an inert loop B-295 to obtain composite 25.
[0154] (Comparative Example 1-1) According to the composition shown in Table 2, NMC and fibrous carbon 100T were mixed at a rotation speed of 1000 rpm for 10 minutes using a high shear multi-function machine Mechanofusion manufactured by Hosokawa Micron Corporation to obtain composite 26.
[0155] (Comparative Example 1-2) According to the composition shown in Table 2, NMC and fibrous carbon dispersion 8 were mixed using a planetary mixer at a rotation speed of 30 rpm for 70 minutes to prepare a mixture. After that, the mixture was dried at 120°C for 2 hours in a hot air oven to obtain composite 27.
[0156] (Comparative Example 1-3) According to the composition shown in Table 2, NMC and fibrous carbon dispersion 9 were mixed using a planetary mixer at a rotation speed of 30 rpm for 50 minutes to prepare a mixture. After that, the mixture was dried at 120°C for 2 hours in a hot air oven to obtain composite 28.
[0157] <Nitrogen element content measurement> The composite to be measured was subjected to XPS analysis to obtain an XPS spectrum. The XPS spectrum was then analyzed to obtain the nitrogen element content in the composite. The XPS apparatus used was a ThermoFisher K-Alpha TM In this analysis, the X-ray was AlKα, and the diameter of the measurement area was 400 μm. The N1s peak due to nitrogen atoms was assigned to a peak near 402 eV.
[0158] <Exothermic peak temperature of fibrous carbon> The exothermic peak temperature of the fibrous carbon was evaluated using a differential thermobalance, ThermoplusEV02TG8121, manufactured by Rigaku Co., Ltd. The exothermic peak temperature obtained when the temperature was raised from 40°C to 800°C at 10°C / min while flowing compressed air at 200mL / min was used as an index. The calculation of the exothermic peak temperature was performed by reading the top temperature of the exothermic peak of the fibrous carbon in the range of 400 to 700°C in the DTA curve obtained by measurement, as shown in FIG. 1 as an example.
[0159] [Table 2]
[0160] <Preparation of positive electrode mixture slurry and positive electrode film> Capacity 150cm 3 Into a plastic container, 18.8 parts of an 8% binder solution (polyvinylidene fluoride resin: W#9300) dissolved in NMP in advance and 12.7 parts of solvent (NMP) were weighed out, and then 68.5 parts of electrode composite 1 were added, and the mixture was stirred at 2,000 rpm for 150 seconds using a planetary centrifugal mixer (Thinky's Awatori Rentaro, ARE-310) to obtain composite slurry 1. The non-volatile content of composite slurry 1 was 70 mass%.
[0161] Composites 2 to 22 and 24 to 28 were treated in the same manner as for composite slurry 1 to obtain composite slurries 2 to 22 and 24 to 28.
[0162] Capacity 150cm 3 Into a plastic container, 10 parts of an 8% binder solution (polyvinylidene fluoride resin: W#9300) previously dissolved in NMP and 20.8 parts of a solvent (NMP) were weighed out, and then 69.2 parts of the electrode composite 23 were added, and the mixture was stirred at 2,000 rpm for 150 seconds using a planetary centrifugal mixer (Thinky's Awatori Rentaro, ARE-310) to obtain a composite slurry 23. The non-volatile content of the composite slurry 23 was 70 mass%.
[0163] The composite slurries 1 to 28 were applied onto aluminum foil with a thickness of 20 μm using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to prepare electrode films. The electrode films were then rolled using a roll press (Thank Metals, 3 t hydraulic roll press) to obtain positive electrodes 1 to 28. The weight per unit area of the composite layer was 20 mg / cm. 2 The density of the composite layer after rolling was 3.2 g / cc.
[0164] <Assembly of a cell for evaluating the positive electrode of a lithium-ion secondary battery> The previously prepared electrode films 1 to 28 were punched out to φ16 mm to be used as the working electrode, and a metallic lithium foil (thickness 0.15 mm) was used as the counter electrode. A separator (porous polypropylene film) was inserted and laminated between the working electrode and the counter electrode, and the electrolyte (a non-aqueous electrolyte in which LiPF6 was dissolved at a concentration of 1M in a mixed solvent in which ethylene carbonate and diethyl carbonate were mixed at a volume ratio of 1:1) was filled to assemble a bipolar sealed metal cell (Hosen HS Flat Cell). The cell was assembled in a glove box substituted with argon gas.
[0165] <Evaluation of rate characteristics of positive electrodes in lithium-ion secondary batteries> The lithium-ion secondary battery positive electrode evaluation cell thus prepared was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant current / constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C and a charge end voltage of 4.2V, constant current discharging was performed at a discharge rate of 0.2C and a discharge end voltage of 2.5V. This operation was repeated three times, and then constant current / constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C and a charge end voltage of 4.2V, and constant current discharging was performed at a discharge rate of 3C and a discharge end voltage of 2.5V. 1C was the current value at which the theoretical capacity of the positive electrode was charged or discharged in 1 hour. The rate characteristic can be expressed by the ratio of the 0.2C discharge capacity to the 3C discharge capacity, as shown in the following formula 1. (Formula 1) Rate characteristic = 3C discharge capacity / 0.2C discharge capacity x 100 (%) A relative value (%) was calculated based on the rate characteristic of Comparative Example 1-2, and evaluated according to the following criteria. Rate characteristic criteria ◎: 150% or more (very good) ○: 130% or more but less than 150% (Excellent) ○△: 110% or more but less than 130% (good) △: 100% or more but less than 110% (defective) ×: Less than 100% (defective)
[0166] <Evaluation of cycle characteristics of positive electrodes in lithium-ion secondary batteries> The lithium-ion secondary battery positive electrode evaluation cell thus prepared was placed in a thermostatic chamber at 25°C, and charge / discharge measurements were performed using a charge / discharge device (Hokuto Denko Corporation, SM-8). After constant current / constant voltage charging (cutoff current: 0.02C current) was performed at a charge rate of 0.2C with a charge end voltage of 4.2V, constant current discharging was performed at a discharge rate of 0.2C with a discharge end voltage of 2.5V. This operation was repeated 200 times. 1C was the current value at which the theoretical capacity of the positive electrode was charged or discharged in 1 hour. The cycle characteristics can be expressed as the ratio of the 3rd 0.2C discharge capacity to the 200th 0.2C discharge capacity, as shown in the following formula 2. (Formula 2) Cycle characteristic = 3rd 0.2C discharge capacity / 200th 0.2C discharge capacity × 100 (%) A relative value (%) was calculated based on the cycle characteristic of Comparative Example 1-2, and the results were evaluated according to the following criteria. Cycle performance criteria ◎: 180% or more (excellent) ○: 150% or more but less than 180% (Excellent) ○△: 120% or more but less than 150% (good) △: 100% or more but less than 120% (defective) ×: Less than 100% (extremely poor)
[0167] [Table 3]
[0168] As shown in Table 3, the Examples showed superior battery characteristics compared to the Comparative Examples. Among them, in Examples 2-6 to 2-9, 11, 18, and 19, in which the detected amount of nitrogen element in the composite was in the most appropriate range, it is presumed that the excellent battery characteristics were shown due to the lower resistance of the electrode, which was due to the effect of improving the adsorption force of the fibrous carbon and the active material by the nitrogen element. In the comparative examples, the amount of nitrogen detected in the composite was outside the range of the present invention, and it is believed that the fibrous carbon caused poor adsorption to the active material, agglomerated, and did not form a uniform composite state, leading to deterioration of the electrode resistance and battery characteristics. From the above, it was demonstrated that the electrode composite of the present invention can exhibit excellent battery characteristics regardless of the production method.
Claims
1. A composite for a secondary battery electrode comprising fibrous carbon and an active material, characterized in that the amount of nitrogen element detected by X-ray photoelectron spectroscopy is 0.05 mol % or more and 10 mol % or less.
2. 2. The secondary battery electrode composite according to claim 1, wherein the fibrous carbon contained in the secondary battery electrode composite has an exothermic peak temperature of 520° C. or less as measured in the presence of oxygen by simultaneous thermogravimetry and differential thermal analysis.
3. 3. The composite for a secondary battery electrode according to claim 1 or 2, further comprising a dispersant, the dispersant containing a copolymer containing an aliphatic hydrocarbon structural unit and a nitrile group-containing structural unit, the aliphatic hydrocarbon structural unit containing an alkylene structural unit, a content of the aliphatic hydrocarbon structural unit being 40 mass% or more and less than 85 mass% based on the mass of the copolymer, and a content of the nitrile group-containing structural unit being 15 mass% or more and 50 mass% or less based on the mass of the copolymer.
4. 4. The composite for a secondary battery electrode according to claim 3, wherein the copolymer further comprises 10% by mass or less of an alkyl group-substituted or unsubstituted carbamoyl group-containing structural unit based on the mass of the copolymer.
5. 3. The composite for a secondary battery electrode according to claim 1, wherein the amount of nitrogen element measured by X-ray photoelectron spectroscopy is 0.3 mol % or more and 3 mol % or less.
6. The composite for a secondary battery electrode according to claim 1 or 2, further comprising a binder resin.
7. 3. A secondary battery electrode comprising the composite for a secondary battery electrode according to claim 1 or 2.
8. A secondary battery comprising the electrode for a secondary battery according to claim 7.
9. A vehicle or device comprising the secondary battery according to claim 8.
10. 2. A method for producing a composite for a secondary battery electrode according to claim 1, comprising the steps of: combining a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent with an electrode active material using a mixing device; and removing the solvent and drying the composite for a secondary battery electrode.
Citation Information
Patent Citations
Lithium-carbon composite negative pole piece, preparation method thereof and lithium secondary battery
CN108598419A
Dispersant, conductive material dispersion, and slurry for electrode film
JP2021122751A
Method for producing composite particles for electrochemical element electrodes, method for producing electrochemical element electrodes, and method for producing electrochemical elements
JP6760065B2
Composite particles for electrochemical element electrodes, electrochemical element electrodes, and electrochemical elements
JP6954424B2
Electrode structure
JP7198331B2